Mercado y medio ambiente: el caso de la soya en la Amazonía brasileña - Pasquis, Richard (2006)
The ongoing process of globalization increases competition between all countries in the international market. Competitiveness becomes the main challenge for commodities-producing regions without concern for social and environmental externalities. In the case of soy markets, Brazil initiated a process of Amazonian land occupation due to their favorable conditions for the growth of agribusiness extension. In addition to the great number of negative environmental consequences already registered, competitiveness is beginning to decline not only for the Amazonian region but also for surrounding agricultural areas.